TFE3-rearranged perivascular epithelioid cell tumors of the head and neck with rare fusion partners: clues to the differential diagnosis between benign and malignant tumors - Yuka Takahashi; Akihiko Yoshida; Seiichi Yoshimoto; Shigenobu Suzuki; Satsuki Kishikawa; Ayaka Mitsui; Eijitsu Ryo; Yuki Kojima; Kan Yonemori; Yasushi Yatabe; Taisuke Mori (Diagnostic Pathology)
Abstract Background Perivascular epithelioid cell tumors (PEComas) rarely appear in the head and neck region. This case report describes two transcription factor E3 (TFE3)-rearranged PEComa cases, consisting of one in the orbit and one in the nasal cavity. Case presentation Both cases demonstrated sheet-like or focal nested architecture and comprised epithelioid cells with abundant clear to eosinophilic cytoplasm and vascular stroma. The first case exhibited partial pleomorphism, a small necrosis area, and slightly increased mitosis and was classified as malignant. The second case demonstrated mild atypia and no mitosis or necrosis and was categorized as benign. The nasal tumor was initially considered a TFE3-rearranged renal cell carcinoma metastasis. However, a subsequent renal tumor biopsy revealed angiomyolipoma. The RNA sequence revealed ZC3H4::TFE3 and PRCC::TFE3 fusions in the first and second cases, respectively. Conclusion The fusion partner gene ZC3H4 is uncommon, and this is the third reported PEComa case. The fusion partner gene PRCC is often reported in TFE3-rearranged renal cell carcinoma, and this PEComa case is the second reported in the head and neck region. The initially reported cases with the fusion partner genes ZC3H4 and PRCC were categorized as malignant. These cases were discussed with a literature review.